Functional dosing of mesenchymal stromal cell-derived extracellular vesicles for the prevention of acute graft-versus-host-disease. (17th February 2020) - Dal Collo, Giada; Adamo, Annalisa; Gatti, Alessandro; Tamellini, Edoardo; Bazzoni, Riccardo; Takam Kamga, Paul; Tecchio, Cristina; Quaglia, Francesca Maria; Krampera, Mauro
Abstract: Graft-vs-host-disease (GvHD) is currently the main complication of allogeneic hematopoietic stem cell transplantation. Mortality and morbidity rates are particularly high, especially in steroid-refractory acute GvHD (aGvHD). Immune regulatory human bone marrow mesenchymal stromal cells (hMB-MSCs) represent a therapeutic approach to address this issue. Unfortunately, their effect is hardly predictable in vivo due to several variables, that is, MSC tissue origin, concentration, dose number, administration route and timing, and inflammatory status of the recipient. Interestingly, human bone marrow MSC-derived extracellular vesicles (hBM-MSC-EVs) display many of the hBM-MSC immunoregulatory properties due to their content in paracrine factors that greatly varies according to the collection method. In this study, we focused on the immunological characterization of hBM-MSC-EVs on their capability of inducing regulatory T-cells (T-regs) both in vitro and in a xenograft mouse model of aGvHD. We correlated these data with the aGvHD incidence and degree following hBM-MSC-EV intravenous administration. Thus, we first quantified the EV immunomodulation in vitro in terms of EV immunomodulatory functional unit (EV-IFU), that is, the lowest concentration of EVs leading in vitro to at least threefold increase of the T-regs compared with controls. Second, we established the EV therapeutic dose in vivo (EV-TD) corresponding to 10-fold the in vitro EV-IFU. According to this approach, we observed a significant improvement of both mouse survival and control of aGvHD onset and progression. This study confirms that EVs may represent an alternative to whole MSCs for aGvHD prevention, once the effective dose is reproducibly identified according to EV-IFU and EV-TD definition. : Abstract : Schematic summary of in vitro definition of extracellular vesicle (EV) immunomodulatory functional unit and EV therapeutic dose for in vivo treatments. Adobe Illustrator software was used to perform the 2D protocol.